Comparative Efficacy of Two Bamboo-Derived Activated Carbons for Hospital Wastewater Remediation - Putu Hadi Setyarini; Hanum Surya Pembayun; Dwi Hadi Sulistyarini; Nuretha Hevy Purwaningtyas; Francisca Gayuh Utami Dewi (Advance Sustainable Science Engineering and Technology, 2025)
Liquid medical waste containing pathogens and hazardous chemicals can pollute the environment and endanger human health. The increasing volume of waste during the COVID-19 pandemic adds urgency to find effective and sustainable treatment methods. However, environmentally friendly and efficient solutions are still limited. This study aims to explore the utilization of activated carbon from two local bamboo species, Gigantochloa apus (GA) and Bambusa vulgaris (BV) as alternative adsorbents in the treatment of liquid medical waste. Two-year-old bamboo was traditionally carbonized and activated using 0.3 M sodium chloride solution. The 50 mesh charcoal powder was tested using BET surface area analysis with QUADRASORB evo™ instrument, morphology using FESEM (FEI Quanta 650), and pollutant reduction efficiency through pH, TDS (HAIK EZ 9909), COD (HACH DBR 200 closed reflux method), and BOD (Winkler method with BOD 6 VELP system) measurements. The results showed that GA activated carbon exhibited a much higher adsorption capacity due to its larger BET surface area compared to BV. In addition, pH and Total Dissolved Solids (TDS) analysis showed that wastewater treated with GA activated carbon exhibited a greater reduction in TDS levels. The study also evaluated the reduction of Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD), which confirmed that GA provided higher pollutant removal efficiency than BV. These findings underscore the potential of GA and BV as effective adsorbents for medical wastewater treatment, offering a sustainable solution to improve water quality and reduce environmental impacts associated with liquid medical waste.